Duszpasterstwo okupowanego Lwowa = Pastoral care of occupied Lvov - Osadczy, Włodzimierz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
After the Soviet aggression in 1939, the Roman Catholic Church found itself under a double ppression: as an institution ideologically hostile to the communist regime and as the custodian of the Polish tradition associated with this city from its inception. For the first time in its history, the Church began to act as a persecuted organization. The deportations of faithful Poles went hand in hand with the closure of church structures.
Keywords: Lvov; Catholic Church; seminary; repression; pastoral ministry; archbishop; Lwów; kościół katolicki; represje; duszpasterstwo; arcybiskup